Synthesis and biological properties of water-soluble polyphenylthiophene brushes with poly(ethylene glycol)/polyzwitterion side chains. Issue 10 (14th February 2017) - Zhang, Yajun; Zhang, Zhengkui; Liu, Changren; Chen, Weizhi; Li, Cheng; Wu, Wei; Jiang, Xiqun
Abstract : Two types of water-soluble polyphenylthiophene brushes with poly(ethylene glycol) and polyzwitterion side chains were synthesized and studied as bioprobes. Abstract : Two types of water-soluble molecular brushes with a poly(3-phenylthiophene) (PPT) backbone tethering poly(ethylene glycol) (PEG) and zwitterionic poly(carboxybetaine) (PCB) side chains were synthesized and named PPTPEG and PPTPCB, respectively. Atomic force microscopy observations demonstrated their wormlike morphology with a length range of 5–33 nm. The two types of molecular brushes had similar emission spectra covering 500–800 nm with a maximal emission wavelength of about 590 nm in water. The fluorescence signals falling in 650–800 nm could penetrate deeper in tissues and improve the imaging properties of the brushes when they were used as optical probes. PPTPEG and PPTPCB brushes could be internalized by cells through caveolae-mediated endocytosis. The effects of PEG and PCB side chains of the brushes on their biological properties were compared, showing that the PCB side chain was favorable to the cellular uptake, tumor penetration and tumor targeting of the molecular brushes.